Localização subcelular da DSCR2, uma proteína relacionada à síndrome de Down - Possik, Patrícia Abrão (Universidade Federal de São Carlos, 2003)
Down Syndrome (DS) is the major cause of mental retardation with a high incidence among human beings. Main features in DS include facial and dermatological features, congenital heart defects as well as immunological, gastrointestinal and endocrine abnormalities. Among a variety of cancer, a 20 fold increased risk of developing leukemia in younger people and an increased risk of testicular cancer is noticeable in DS patients. Most DS patients carry a complete trisomy of chromosome 21, but patients carrying a partial trisomy have also been observed. Analyses of partial trisomy of chromosome 21 have helped determining the minimal regions potentially associated with DS features. The DSCR2 gene located in the so-called Down Syndrome Critical Region 2 (DCR-2) codes a 32.8-kDa leucine-rich protein comprised of 34% hydrophobic amino acid residues. Little is known about the DSCR2 protein characteristics but many assumptions have been made according to in silico predictions. In this work, we used immunocytochemical and fluorescence assays to investigate the subcellular location of the protein encoded by the DSCR2 gene in transfected cells. It was previously suggested that DSCR2 was located in the plasma membrane as an integral protein. Interestingly, we observed this protein in the endoplasmic reticulum of cells. We also studied whether the location of DSCR2 truncated forms had different subcellular distribution and our observations indicate that it is probably not inserted in inner membranes once the fragments lacking the predicted transmembrane helices remained in the ER. We suggest that DSCR2 is located in the cytoplasmic side of endoplasmic reticulum by indirect interaction with the ER membrane or with another protein.
Keywords: Biologia molecular; Down, Síndrome de; Localização subcelular; DSCR2; Cromossomo 21; Retículo endoplasmático; CIENCIAS BIOLOGICAS::GENETICA